Cancer profiles by affinity propagation. (5th October 2009) - Soria, D.; Garibaldi, J.M.; Ambrogi, F.; Boracchi, P.; Raimondi, E.; Biganzoli, E.
The affinity propagation algorithm is applied to various problems of breast and cutaneous tumours subtyping using traditional biologic markers. The algorithm provides a procedure to determine the number of profiles to be considered. Well-known breast cancer case series and cutaneous melanoma were used to compare the results of the affinity propagation with the results obtained with standard algorithms and indexes for the optimal choice of the number of clusters. Results from affinity propagation are consistent with the results already obtained having the advantage of providing an indication about the number of clusters.